Indirect taxation of monopolists: A tax on price - Henrik Vetter (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
A digressive tax such as a variable rate sales tax or a tax on price gives firms an incentive for expanding output. Thus, unlike unit and ad valorem taxes which amplify the harm from monopoly, a digressive tax lessens the harm. We analyse a tax on price with respect to efficiency and practical policy appeal. In particular, we show how tax reforms based only on observation of price and quantity can make use of a tax on price in order to improve welfare. That is, it is practical to use a tax on price. The argument extends to fixed-number homogenous oligopoly.
Keywords: H21; L13; 330; tax on price; ad valorem tax; tax incidence; Preis; Steuer; Umsatzsteuer; Steuerwirkung; Monopol; Ramsey-Preis; Theorie